(untitled) (Global Journal of Science Frontier Research, 2017)
The physical principle of the work of Van de Graaff generator, until now, is not explained, but there is only a technical oscillator circuit. There are no calculated relationships, which give the possibility to calculate this generator. In the article physical oscillator circuit and its mathematical model is represented, and it is also shown that the principle of its operation is based on the use of a law of parametric self-induction. Are obtained the calculated relationships, which make it possible to calculate the parameters of generator. Collectorless generators and multipliers of constant stress are examined.